Non-isothermal cure kinetics of aerogel/epoxy composites using differential scanning calorimetry - Krishnaswamy, Suryanarayanan; Marchante, Veronica; Abhyankar, Hrushikesh; Huang, Zhaorong; Brighton, James (Taylor and Francis, 2019)
The present work determines the non-isothermal cure parameters of aerogel/epoxy samples along with the effect of a wetting agent. The cure parameters were calculated using Kissinger and isoconversional methods after which the reaction was modeled with the Sestak–Berggren equation. It is seen that the composites had higher activation energy and frequency factor values compared to the pure resin, and similarities in cure parameters between the aerogel/epoxy composites with and without the wetting agent were seen. Hence, the former’s use is advocated due to its positive influence on the resin–aerogel interface without sacrificing the cure parameters.
Keywords: aerogel; epoxy; cure kinetics; DSC; activation energy